Zuojin Pill ameliorates chronic atrophic gastritis induced by MNNG through TGF-β1/PI3K/Akt axis. (10th May 2021) - Tong, Yuling; Wang, Ruilin; Liu, Xia; Tian, Miao; Wang, Yanling; Cui, Yanfei; Zou, Wenjun; Zhao, Yanling
Abstract: Ethnopharmacological relevance: Zuojin Pill (ZJP) is a classic prescription composed of Coptis chinensis and Tetradium ruticarpum (A.Juss.) T.G.Hartley, which is often used in the treatment of digestive system diseases. Aim of this study: The purpose of this study was to explore the therapeutic effect and potential mechanism of ZJP on chronic atrophic gastritis (CAG) induced by MNNG. Materials and methods: The GES-1 and rat model of CAG was established by MNNG. Detection of cell viability, morphological changes and proliferation of GES-1 by CCK-8 and high content screening (HCS) assay. G-17, IL-8 and TNF-α in rat serum were detected by ELISA kit. The expression of related mRNA and protein on TGF-β1/PI3K/Akt signal axis were detected by RT-PCR and Western blot. Results: The results showed that ZJP could significantly improve the GES-1 damage induced by MNNG and improve the gastric histomorphology of CAG rats. The intervention of ZJP could significantly reduce the content of G-17 and inflammatory factors IL-8, TNF- α, IL-6 and IL-1β, inhibit the expression of TGF-β1, PI3K and their downstream signals p-Akt, p-mTOR, P70S6K, and promote the expression level of PTEN, LC3-II and Beclin-1. Conclusion: ZJP has a good therapeutic effect on CAG induced by MNNG, which may be closely related to the inhibition of TGF-β1/PI3K/Akt signal pathway. Graphical abstract: Image 1